Pengelolaan Keuangan Desa Melalui E-Village Budgeting di Kabupaten Banyuwangi - Munfarida Rizky Mutamimmah; Alwan Sri Kustono; Rochman Effendi (UPT Penerbitan Universitas Jember, 2018)
This study aims to determine village financial management in Srono Sub District of Banyuwangi District by using e-Village Budgeting system and the effectiveness of using that system. This study uses primary data was collected from respondent’s answers on interview was conducted with the parties concerned on village financial management in Srono Sub District of Banyuwangi District. Methods of data analysis is using descriptive with qualitative approaches and triangulation as a test of data validity. The results showed that village financial management by e-Village Budgeting consists of the process of planning, administration, and accountability of APBDesa. By using e-Village Budgeting village financial management becomes more effective and efficient. Keywords : e-Village Budgeting, Management and Village Financial